Reclassification of Lamprotula rochechouartii as Margaritifera rochechouartiicomb. nov. (Bivalvia Margaritiferidae) revealed by time-calibrated multi-locus phylogenetic analyses and mitochondrial phylogenomics of Unionoida - Huang, Xiao-Chen (Molecular phylogenetics and evolution, 2018)
The family Margaritiferidae encompasses 12 valid species, which are distributed widely but disjunctively in the Northern Hemisphere. A lack of a well resolved and temporally calibrated phylogenetic framework of Margaritiferidae has made it difficult to discuss the evolutionary pattern and process. Phylogenetic relationships between five major clades, which were revealed in earlier studies, remain elusive and unresolved. Lamprotula rochechouartii has long been classified within the family Unionidae based on shell morphology, but our preliminary molecular study on this species made us hypothesize that it has an affinity with margaritiferids. Hence, five loci (COI, 16S, 18S, 28S and histone H3) were used to investigate the phylogenetic position of L. rochechouartii and intra-familial relationships within Margaritiferidae using various partitioning strategies. Moreover, two mitochondrial genomes were newly obtained to further resolve and validate the five-clade relationships within Margaritiferidae in a broad view of Unionoida evolution. Both five-gene and mitogenome datasets strongly advocated treating Lamprotula rochechouartii as Margaritifera rochechouartiicomb. nov. Maximum likelihood and Bayesian inference analyses using partitioned five-gene dataset resulted in various topologies, but five well-supported clades were obtained. The most probable cladistic relationships generated by five-gene dataset analyses were identical to subsequent whole mitogenome analyses except the position of M. monodonta. M. rochechouartii and M. laosensis had a well-supported sister relationship and formed a basal clade splitting from the rest of the family. Based on six reliable fossils, crown age of the extant Margaritiferidae was estimated during the Late Cretaceous at 88.3 Ma (95% HPD=66.2-117.4). But we hypothesized a much earlier origin of this family due to the Permian stem age (mean=257Ma, 95% HPD=230.0-296.0) and a high extinction rate in the whole order. Biogeographic scenarios supported a Laurasian origin of extant Margaritiferidae during the Late Cretaceous, and suggested that Asian margaritiferids may have had two origins, having either Asia (M. rochechouartii, M. laosensis) or North America (M. dahurica, M. laevis, and M. middendorffi) as ancestral. The newly added Margaritiferidae species M. rochechouartii expands our recognized distribution range of modern margaritiferids. Our results indicate that whole mitogenome sequences can be used to reconstruct robust phylogenetic relationships for freshwater mussels, especially with the help of adding M-type mitogenomes.